Analisis Penggunaan Material Kaca pada Dinding Luar Bangunan Tinggi Untuk Meminimalisir Penggunaan Energi pada Bangunan - Muhammad Fadly Saleh; Fifi Elfira Sirajuddin (Celebes Engineering Journal, 2019)
Building is a huge of energyuser, both at the time of construction and operational, making the building one of the causes of global warming. This study aims to analyze the types of building window glass to obtain the best type of glass in minimizing energy use in buildings. This research is a quantitative research with observation and experimental methods. The object of this research is the building of Makassar Four Points Hotel that is located atJalan Andi Djemma, Makassar City. Observationswere conducted on the physical building in the form of design drawings and conditions at the location of the building project. Experimentation were conducted on the results of observations by analyzing several types of window glass by using the eQuest computer program energy simulation. After changing the type of building windows of the Four Points Hotel Makassar, the energy consumption of buildings on a typical floor has decreased to 10.04% from the existing. The type of window glass used is double clear reflective glass (glass: ¼ in, air: ½ in).